2011
DOI: 10.1021/jp1094454
|View full text |Cite
|
Sign up to set email alerts
|

Band Gap Tuning of Hydrogenated Graphene: H Coverage and Configuration Dependence

Abstract: The electronic states of partially hydrogenated graphene (HG) structures are studied by the density functional theory calculations. Several types of HG configurations, including randomly removing of H pair, randomly removing individual H atoms, and ordered H pairs removal, are investigated. We find that the configurations with randomly removing H pairs are most energetically favorable. More interestingly, the band gap for such configurations decrease with H concentration and approaches zero around 67% H covera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
144
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 180 publications
(157 citation statements)
references
References 47 publications
10
144
2
1
Order By: Relevance
“…The obtained level of hydrogenation is in good agreement with experimental results and corresponds with the insulator structure (calculated band gap is 1.7 eV). Because the band gap of hydrogenated 1LG depends on hydrogen coverage, 32 we can engineer the electronic structure of hydrogenated 1LG in a wider range and enhance its applications in electronics (electrical properties of hydrogenated 1LG, Supplementary Figure S11b) and photonics by introducing negative AFM lithography.…”
Section: Electrical Control Of Nanoscale Functionalization I-s Byun Ementioning
confidence: 99%
“…The obtained level of hydrogenation is in good agreement with experimental results and corresponds with the insulator structure (calculated band gap is 1.7 eV). Because the band gap of hydrogenated 1LG depends on hydrogen coverage, 32 we can engineer the electronic structure of hydrogenated 1LG in a wider range and enhance its applications in electronics (electrical properties of hydrogenated 1LG, Supplementary Figure S11b) and photonics by introducing negative AFM lithography.…”
Section: Electrical Control Of Nanoscale Functionalization I-s Byun Ementioning
confidence: 99%
“…Interestingly, theoretical calculation showed that the bandgap of hydrogenated graphene can be continuously tuned from 0 to 4.66 eV by different H coverage [8] . These results provide a new perspective to the application of graphene-based materials as the acceptor in the polymer solar cells field.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The chemical modification of graphene is fundamental for tailoring its physical and chemical properties. [3][4][5][6][7] In particular, the interaction of water with graphene is receiving much interest. [8][9][10][11][12][13][14][15] Water molecules adsorbed on graphene act as dopants without remarkable changes in electron mobility.…”
Section: Introductionmentioning
confidence: 99%